2013
DOI: 10.7314/apjcp.2013.14.11.6375
|View full text |Cite
|
Sign up to set email alerts
|

GSTP1 Gene Ile105Val Polymorphism Causes an Elevated Risk for Bladder Carcinogenesis in Smokers

Abstract: Background: The glutathione S transferase (GST) family of enzymes plays a vital role in the phase II biotransformation of environmental carcinogens, pollutants, drugs and other xenobiotics. GSTs are polymorphic and polymorphisms in GST genes have been associated with cancer susceptibility and prognosis. GSTP1 is associated with risk of various cancers including bladder cancer. A case control study was conducted to determine the genotype distribution of GSTP1 A>G SNP, to elucidate the possible role of this SNP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Finally, 85 articles (19,604 cases and 23,710 controls) were kept (Fig. 1), of which 70 articles (16,131 cases and 19,696 controls) were about the relationship between GSTM1 and cancers [4,5,16,17,24–89] (Table 1); 49 articles (11,555 cases and 14,606 controls) were about the relationship between GSTT1 and cancers [4,5,16,24,25,27–31,33,34,36–39,41,42,44–49,51,52,56,58,60,61,63,65–68,70,74–76,79,80,82–85,87,88,90–93] (Table 2); and 31 articles (8518 cases and 9884 controls) were about GSTP1 and cancers [5,16,17,24,30,31,34,36,42,44,45,47,49,52,59,66,67,70,79,88,94–103] (Table 3) among smokers. Among these researches, 8 articles mentioned the classification of smoking levels (20 pack-year).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 85 articles (19,604 cases and 23,710 controls) were kept (Fig. 1), of which 70 articles (16,131 cases and 19,696 controls) were about the relationship between GSTM1 and cancers [4,5,16,17,24–89] (Table 1); 49 articles (11,555 cases and 14,606 controls) were about the relationship between GSTT1 and cancers [4,5,16,24,25,27–31,33,34,36–39,41,42,44–49,51,52,56,58,60,61,63,65–68,70,74–76,79,80,82–85,87,88,90–93] (Table 2); and 31 articles (8518 cases and 9884 controls) were about GSTP1 and cancers [5,16,17,24,30,31,34,36,42,44,45,47,49,52,59,66,67,70,79,88,94–103] (Table 3) among smokers. Among these researches, 8 articles mentioned the classification of smoking levels (20 pack-year).…”
Section: Resultsmentioning
confidence: 99%
“…Cytochrome P450 (CYP) is the most important phase I enzymes system, which is usually involved in the activation of carcinogens; and phase II enzymes, particularly N-acetyltransferase (NAT) and glutathione s-transferase (GSTs), which mostly detoxify the products to be excreted in the urine and possibly played an important role in cancer etiology (Steck and Hebert, 2009;Zgheib et al, 2010). Although studies suggested that CYP2E1 genetic polymorphisms have an impact on the incidence of cancer (Danko and Chaschin, 2005), epidemiological studies suggest that the NAT1, NAT2, GSTM1 and GSTP1 polymorphisms modify the risk of developing cancers of the urinary bladder Pandith et al, 2013;Zabost et al, 2013). Therefore, not only is CYP2E1 suspected to be involved with the development of bladder cancer, but also other DMEs genetic factors may be associated with bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Since these molecules contribute to the metabolism of potential carcinogens, any polymorphism affecting their expression or function may lead to cancer [31]. Most articles show that in most populations, the GSTM1 null genotype [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] and rs1695 in GSTP1 [16,19,33,40,42,[48][49][50][51][52][53][54][55] increase the risk for BC. However, a Chinese study showed that the GSTT1 null genotype was associated with a decreased risk for BC [36].…”
Section: Chemical Carcinogenesismentioning
confidence: 99%